1‐methylcyclopropene potentials in maintaining the postharvest quality of fruits, vegetables, and ornamentals: A review. Issue 1 (12th December 2020) - Baswal, A K; Ramezanian, Asghar
Abstract: 1‐Methylcyclopropene (1‐MCP) application influences the post‐harvest ripening process in numerous horticultural crops by inhibiting the ethylene perception as it competes with ethylene for binding receptors and thereby retards the down regulation processes. Successful commercialization of 1‐MCP requires a balance between its concentration to be applied, exposure time and type of crop. This review article describes 1‐MCP application for maintaining the post‐harvest quality in selected horticultural crops. Practical applications: This review article delivers key information as how 1‐MCP application significantly influenced the post‐harvest quality of selected horticultural crops in recent years. Furthermore, this review article would also address different factors influencing the response to 1‐MCP which would expand more knowledge among growers for its successful application.